(untitled) (International Journal of Studies in Nursing, 2018)
The shortage of nurses in Saudi Arabia like many other countries in the world is a problem. Additionally, there are a unique socio-cultural factor that causes the problem including but not limited to the negative perceptions and attitudes towards nurses. Unfortunately, the apprentices are subjected to a system that is inadequately represented by long working hours, negative images, and work pressures. In addition, several factors are attributed to the problems the students face during the initial year of clinical education. This study will analyze and evaluate the different factors that influence the clinical education of the bachelor nursing apprentices, particularly in the first year of experience. Aims and Objectives: The purpose of this study is to explore the factors affecting the clinical practice of nursing interns at tertiary hospital Jeddah. Methodology and Methods: The research was employed as a qualitative approach. Bachelor nursing students who are currently undertaking their internship program in a tertiary hospital Jeddah) were recruited as participant in this study. Findings: Data analyses regarding the factors affecting the clinical practice of nursing interns are summarized both positively and negatively. The major theme that emerged that reflects the positive experiences of intern students was “a time for reflection”. Further to this the major theme that emerged relating to the challenges experienced by student interns was “cold environment’. Conclusions: The findings of this research contribute to our understanding of factors affecting the clinical practice of nursing interns. Students identified their clinical learning as cold learning environment because they were treated unfairly, ignored by their instructors and were being embarrassed and feeling restricted. Moreover, students have also identified positive experiences for them during their internship program. The internship program is a great chance for the student for a reflection.